Republic of Estonia : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Estonia. (IMF Staff Country Reports; Country Report, 2017)
This 2016 Article IV Consultation highlights that Estonia's recent growth has been subdued. Labor productivity and external competitiveness have weakened. Growth in 2016 is estimated at only 1.3 percent, driven mainly by private consumption on the back of strong wage growth in a tightening labor market. Exports are gradually recovering, but investment continues to contract. Import growth is accordingly low, keeping the current account in small surplus. Inflation rose moderately to about 1 percent. The economy should gradually strengthen going forward, as the external environment improves and existing pro-growth policies come to fruition. Growth is projected at 2.3 percent and 2.8 percent for 2017 and 2018, respectively.